Distance-dependent association of affect with pacing strategy in cycling time trials - Jones, H. S.; Williams, E. L.; Marchant, D.; Sparks, S. A.; Midgley, A. W.; Bridge, C. A.; McNaughton, L. (Medicine & Science in Sports & Exercise, 2015)
The psychological construct of affect is proposed to significantly contribute to pacing decisions during exercise. Borg`s RPE scale, another important regulator of work rate, is criticized as an inadequate measure of the multiple perceptual responses experienced. This study aimed to examine power output distribution and associated changes in affect, self-efficacy, perceptual cues, HR, and respiratory gases during both 16.1- and 40-km self-paced cycling time trials (TT). Secondly, the differentiation between physical perceptions of exertion and sense of effort in self-paced exercise was investigated.